Peran Media Pembelajaran Interaktif Dalam Meningkatkan Partisipasi Peserta Didik - Reyza Qurrota Akyuna; Ana Dwi Wahyuni; Diyah Mintasih (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This systematic literature review aims to analyze the role of interactive learning media in increasing student participation. This study examines scientific literature from 2020-2025 that is relevant to interactive learning media and student participation. The stages of data content analysis include data collection, data reduction, data presentation, and conclusion drawing. Research results indicate that interactive learning media significantly impacts cognitive ability enhancement, learning motivation, and possesses high levels of validity and practicality. Interactive media proves capable of transforming learning dynamics from passive learning to active learning environment through multi-sensory learning experiences that accommodate diverse student learning styles. Research conclusions confirm that interactive learning media functions as a participatory catalyst that activates students' multiple intelligences, yet its success requires continuous support of technological infrastructure, educator competence, and institutional commitment.